Az ifjúsági munkanélküliség csökkentési lehetőségei atipikus foglalkoztatási formákkal - Oláh Judit; Fónai Eszter (Egyesület Közép-Európa Kutatására Szeged, 2014)
From the beginning of the last decade significant research attention is focused on youth labor market. In recent years, the education level of young people increased. But unemployment among young people has increased both because the economy is becoming more and more labor-saving. On the other hand, there is a significant difference between employers' human resource needs and the young people's expertise, experience. This affects badly their chances of enrollment. In our research, we analyze the non-standard forms of employment. And we try to shed light on the possibility of this form of job creation for young people. The growths of different types of atypical forms of employment do not mean the decrease of the typical, „normal" forms of employment. It rather focuses on a gap and creates work places where traditional full-time, indefinite work contract is not economically practicable. From the non-standard forms of employment in our country the part time jobs show the highest rate of employment which is suitable for students, pensioners and people with changed working abilities who are not capable for full-time jobs.
Keywords: Társadalomtudományok; Közgazdasági és gazdálkodástudományok